2022
DOI: 10.3390/biomedicines10051186
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Potential Hair Growth-Promoting Effect of Botryococcus terribilis, Its Novel Compound Methylated-Meijicoccene, and C32 Botryococcene on Cultured Hair Follicle Dermal Papilla Cells Using DNA Microarray Gene Expression Analysis

Abstract: A person’s quality of life can be adversely affected by hair loss. Microalgae are widely recognized for their abundance and rich functional components. Here, we evaluated the hair growth effect of a green alga, Botryococcus terribilis (B. terribilis), in vitro using hair follicle dermal papilla cells (HFDPCs). We isolated two types of cells from B. terribilis—green and orange cells, obtained from two different culture conditions. Microarray and real time-PCR results revealed that both cell types stimulated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Based on the above, BTEE is anticipated to be employed as a raw ingredient in nutraceuticals and functional foods to prevent or treat chronic inflammation as well as in cosmetics. According to our previous studies, the key components of BTEE include hydrocarbons, botryococcene, and methylated-meijicoccene, which have potential hair growth-promoting and anti-stress benefits [ 17 , 18 ]. We also examined the anti-inflammatory effects of botryococcene and methylated-meijicoccene on the LPS-mediated inflammatory responses in RAW264 cells; however, no significant effects were observed in the range of treatment concentrations of these compounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the above, BTEE is anticipated to be employed as a raw ingredient in nutraceuticals and functional foods to prevent or treat chronic inflammation as well as in cosmetics. According to our previous studies, the key components of BTEE include hydrocarbons, botryococcene, and methylated-meijicoccene, which have potential hair growth-promoting and anti-stress benefits [ 17 , 18 ]. We also examined the anti-inflammatory effects of botryococcene and methylated-meijicoccene on the LPS-mediated inflammatory responses in RAW264 cells; however, no significant effects were observed in the range of treatment concentrations of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Lyophilized powder of BT TEPMO-26 (100 mg) was extracted with 1 mL of 70% Ethanol at room temperature and in the dark for two weeks [ 17 ]. After the extraction, the sample was centrifuged at 1000× g for 10 min, and the supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…braunii (i.e. the B race) based on subsequent studies analyzing hydrocarbon content and phylogenetic placement [ 103 , 104 ]. Additionally, phylogenetic studies [ 9 , 20 ] have shown that B .…”
Section: Future Directionsmentioning
confidence: 99%